Radiation Recall Dermatitis in Breast Cancer Patient after Trastuzumab: A Case Report with Review of Literature - Vadgaonkar, Rohit Avinash; Ventrapati, Pradeep; Mehta, Ankita; Dutta, Anupurva (Indian Journal of Medical and Paediatric Oncology, 2023)
Radiation recall dermatitis (RRD) is an extremely rare phenomenon. A variety of factors such as antineoplastic agents, pharmaceutical agents, physical and environmental factors have been proposed to be the underlying cause of RRD. Only a handful cases have been reported till date, where trastuzumab is sought to be the triggering agent. The presentation of RRD varies from mild erythematous to extensive confluent dermatitis, resolving over a period of 1 to 2 weeks with conservative management. Most of the patients tend to tolerate rechallenge well without showing reappearance. We hereby describe a lady with breast cancer having RRD following administration of trastuzumab. She developed reaction 28 days post-radiotherapy and managed conservatively. Furthermore, she was rechallenged with the same dose, that she tolerated very well, without any reappearance. Hence, an acquaintance of the clinicians to this rare entity is essential for timely diagnosis and appropriate management.
Keywords: radiation recall dermatitis; trastuzumab; radiation recall phenomenon